GRHL1 acts as tumor suppressor in neuroblastoma and is negatively regulated by MYCN and HDAC3 - Fabian, Johannes; Lodrini, Marco; Oehme, Ina; Schier, Marie Catherine; Thole, Theresa Maria; Hielscher, Thomas; Kopp-Schneider, Annette; Opitz, Lennart; Capper, David; Deimling, Andreas von; Rettig, Inga Edeltraud; Milde, Till; et al. (Cancer research, 2014)
Neuroblastoma is an embryonic solid tumor of neural crest origin and accounts for 11% of all cancer-related deaths in children. Novel therapeutic strategies are therefore urgently required. MYCN oncogene amplification, which occurs in 20% of neuroblastomas, is a hallmark of high risk. Here, we aimed to exploit molecular mechanisms that can be pharmacologically addressed with epigenetically modifying drugs, such as histone deacetylase (HDAC) inhibitors. Grainyhead-like 1 (GRHL1), a gene critical for Drosophila neural development, belonged to the genes most strongly responding to HDAC inhibitor treatment of neuroblastoma cells in a genome-wide screen. An increase in the histone H4 pan-acetylation associated with its promoter preceded transcriptional activation. Physically adjacent, HDAC3 and MYCN colocalized to the GRHL1 promoter and repressed its transcription. High-level GRHL1 expression in primary neuroblastomas correlated on transcriptional and translational levels with favorable patient survival and established clinical and molecular markers for favorable tumor biology, including lack of MYCN amplification. Enforced GRHL1 expression in MYCN-amplified neuroblastoma cells with low endogenous GRHL1 levels abrogated anchorage-independent colony formation, inhibited proliferation, and retarded xenograft growth in mice. GRHL1 knockdown in MYCN single-copy cells with high endogenous GRHL1 levels promoted colony formation. GRHL1 regulated 170 genes genome-wide, and most were involved in pathways regulated during neuroblastomagenesis, including nervous system development, proliferation, cell-cell adhesion, cell spreading, and cellular differentiation. In summary, the data presented here indicate a significant role of HDAC3 in the MYCN-mediated repression of GRHL1 and suggest drugs that block HDAC3 activity and suppress MYCN expression as promising candidates for novel treatment strategies of high-risk neuroblastoma. Cancer Res; 74(9); 2604-16. ©2014 AACR.
Gesehen am 16.09.2020